2007
DOI: 10.2337/dc06-1357
|View full text |Cite
|
Sign up to set email alerts
|

Initiate Insulin by Aggressive Titration and Education (INITIATE)

Abstract: OBJECTIVE -Insulin is often postponed for years because initiation is time-consuming. We sought to compare initiation of insulin individually and in groups with respect to change in A1C and several other parameters in type 2 diabetic patients. RESEARCH DESIGN AND METHODS-A randomized (1:1), multicenter, two-arm, parallel design study with a recruiting period of up to 14 weeks and a 24-week treatment period. Either in groups of 4 -8 or individually, using the same personnel and education program, 121 insulin-na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
125
3
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(132 citation statements)
references
References 13 publications
1
125
3
2
Order By: Relevance
“…EXE was titrated to a maximum dose of three times (TID) 20 μg, or the maximum tolerated dose, when HbA1c value at two consecutive visits ranged between 7.1 and 7.5%, or when HbA1c was >7.6% at any given visit. Patients randomised to GLAR started with an initial dosage of 10 IU once daily (QD) at bedtime, followed by self-adjustment of the daily dose according to a fixed-dose treat-to-target (fasting plasma glucose (FPG) <5.6 mmol/L)) algorithm, as described previously (13). Loss of glucose control was defined by fasting blood glucose concentrations greater than or equal to 12.2 mmol/L for 4 or more days out of 7 days during the study, with the increase in glucose concentrations not secondary to a readily identified inter-current illness or pharmacological treatment.…”
Section: Methodsmentioning
confidence: 99%
“…EXE was titrated to a maximum dose of three times (TID) 20 μg, or the maximum tolerated dose, when HbA1c value at two consecutive visits ranged between 7.1 and 7.5%, or when HbA1c was >7.6% at any given visit. Patients randomised to GLAR started with an initial dosage of 10 IU once daily (QD) at bedtime, followed by self-adjustment of the daily dose according to a fixed-dose treat-to-target (fasting plasma glucose (FPG) <5.6 mmol/L)) algorithm, as described previously (13). Loss of glucose control was defined by fasting blood glucose concentrations greater than or equal to 12.2 mmol/L for 4 or more days out of 7 days during the study, with the increase in glucose concentrations not secondary to a readily identified inter-current illness or pharmacological treatment.…”
Section: Methodsmentioning
confidence: 99%
“…During the other treatment period, patients were treated with insulin glargine, started at an initial dose of 10 IU q.d. Patients were instructed to increase the daily dose based on their fasting self-monitored blood glucose levels according to a predetermined treat-to-target algorithm (16).…”
Section: General Experimental Protocolmentioning
confidence: 99%
“…80 In one randomized controlled trial, self-titration was taught to individuals and to groups, with the two approaches achieving similar reductions in HbA 1c (1.8% and 2.0% respectively); the group sessions required half the time. 81 Regarding titration of bolus insulin, simple titration based on postprandial values was as effective as carbohydrate counting, lowering HbA 1c by 1.5%. 83 The principles of insulin titration are described in Box 2, and sample protocols for insulin titration are described in Table 3.…”
Section: Who Should Initiate and Titrate Insulin?mentioning
confidence: 99%
“…78−83 Pa tients using these self-titration algorithms coupled with daily blood glucose monitoring were able to achieve HbA 1c levels similar to those achieved in clinics, reducing their HbA 1c by 1.0% to 2.5%. A variety of insulin types were used in these studies, including 30/70 twice-daily insulin, 79 detemir once daily, 80 glargine once daily 78,81 and rapidacting insulin before meals. 83 Self-titration by patients resulted in similar rates of hypoglycemia compared with physician-managed titration, even though the patients used higher doses of insulin (0.59 units/kg v. 0.40 units/kg).…”
Section: Who Should Initiate and Titrate Insulin?mentioning
confidence: 99%